Treatment of Advanced-Stage Large Cell Neuroendocrine Cancer (LCNEC) of the Lung: A Tale of Two Diseases - Atieh, Tahani; Huang, Chao H. (Frontiers in Oncology, 2021)
LCNEC of the lung comprises a small proportion of the non-small cell lung cancer (NSCLC). Traditionally, they have been classified based on histologic and immunohistochemistry characteristics with features of small cell lung cancer (SCLC) and non-small cell lung cancer. The treatment outcome of advanced-stage LCNEC of the lung is poor with response rates ranging from 34% to 46% with platinum doublets, median progression-free survival(mPFS) ranging between 4.4m to 5.8m, and median overall survival (mOS) ranging from 8m to 12.6m. Recently, genomic profiling with Next Generation Sequencing (NGS) of pulmonary LCNEC can subclassify them as SCLC-like or NSCLC-like. Treatment based on this sub-classification improved outcome by tailoring the treatment using SCLC and NSCLC regimen based on their genomic profile in retrospective analysis. Future studies in LCNEC of the lung, should incorporate this new molecular sub-classification as stratification and possibly include SCLC-like LCNEC into SCLC studies and NSCLC-like into NSCLC studies.